Preparation and photoluminescence enhancement of Li＋ and Eu3＋ co-doped YPO4 hollow microspheres - 张立新 酒红芳 付跃华 孙益新 王瑗钟 (Journal of rare earths, 2013)
Li＋ and Eu3＋ co-doped YPO4 hollow microspheres were successfully synthesized by a sacrificial template method using polystyrene （PS） as template. Techniques of X-ray diffraction （XRD）, scanning electron microscopy （SEM）, as well as transmission electron microscopy （TEM） were employed to characterize the as-synthesized sample. Furthermore, the photoluminescence （PL） characterization of the Li＋ and Eu3＋ co-doped YPO4 microsphere was carried out and the effects of the doping concentration of Li＋ and Eu3＋ active center concentration as well as calcination temperature on the PL properties were studied in detail. The results showed that the incorporation of Li＋ ions into the YPOa：Eu3＋ lattice could induce a remarkable improvement of the PL intensity. The highest emission intensity was observed with the compound of 5%Li＋ and 5%Eu3＋ co-doped YPO4, whose brightness was increased by a factor of more than 2.2 in comparison with that of the YPO4：5%Eu3＋.